METAPHORS ANALYSIS ON STRATEGIC FINANCIAL MANAGEMENT BOOK WRITTEN BY ROBERT ALAN HILL - Tumanggor, Orli Binta; Siahaan, Desta Gloria; Tarigan, Surya Setiadi; Tampubolon, Jonris (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2023)
The purpose of this study was to obtain the metaphor analysis on strategic financial management book. The title of the book is “Strategic Financial Management: Part 1”. This book was written by Robert Alan Hill contains of four chapters, and chapter one was conciously selected to be analysed because it introduced the general information about finance as drawn on the book’s title. Having analyzed chapter one in Strategic Financial Management: Part 1, it was found 22 items of conceptual metaphors. The dominantly domain used was about human, finance, war and company.